Theoretical Foundations and Interplay of Contrastive Linguistics and Translation Studies in Language Learning - Kamolov Dilshod Khusniddinovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the theoretical foundations of contrastive linguistics and translation studies, emphasizing their role within the broader field of linguistics and applied translation. Contrastive linguistics is analyzed as a branch focusing on identifying similarities and differences between languages, while translation studies is viewed as an interdisciplinary science addressing the process, theory, and practice of translation. The article highlights their mutual interdependence, methodological frameworks, and their importance for language teaching, cultural exchange, and professional translation. The findings suggest that both disciplines, although independent in scope, complement one another in promoting effective cross-linguistic and cross-cultural communication.